Recurrent laryngeal nerve injury in conventional thyroid surgery - MN, Muhammad Danial; Mahno, Noor Ezmas; Termizi, Sahrol Azmi (Faculty of Medicine Universiti Kebangsaan Malaysia, 2023)
Introduction: Recurrent laryngeal nerve (RLN) injury in conventional thyroid surgery can happen in 1.5-14% of cases. The outcomes of RLN injury can range from mild hoarseness to upper airway obstruction leading to tracheostomy or intubation. Materials and Methods: This is a retrospective review conducted among patients that undergone thyroid surgery in the SASMEC @IIUM from 2018- 2022. Demographic data, pathological findings, type of operation and visual identification of nerve were recorded. Factors predisposed to recurrent laryngeal nerve injury were evaluated. Preoperative laryngoscopy was performed on all patients. Descriptive analyses were performed. Results: A total of 59 nerves at risk were involved and 16 recurrent laryngeal nerve injuries were recorded. Post- operative laryngoscopy is only done when clinical suspicion of recurrent laryngeal nerve injury arises. Malignancy, size of tumor, reoperation was among the factors identified as the possible risk factors. Conclusion: The risk of recurrent laryngeal nerve injury may rise in malignancy, size of tumor and re-operation.